Cost-Effectiveness Analysis of Out-Of-Hospital versus In-Hospital Extracorporeal Cardiopulmonary Resuscitation for Out-Hospital Refractory Cardiac Arrest - Daoud Al-Badriyeh (832403) (2022)
It has been speculated that out-of-hospital cardiac arrest (OHCA) patients’ survival might be improved by implementing extracorporeal cardiopulmonary resuscitation (ECPR) before arrival to hospital. Therefore, we sought to assess the cost-effectiveness of OH-ECPR versus in-hospital (IH)-ECPR in OHCA patients in Qatar. From the hospital perspective, a conventional decision-analytic model was constructed to follow up the clinical and economic consequences of OH-ECPR versus IH-ECPR in a simulated OHCA population over one year. The primary outcome was the survival at discharge after arrest as well as the overall direct healthcare costs of managing OHCA patients. The robustness of this model was evaluated via sensitivity analyses. The OH-ECPR yielded 16% survival at discharge after arrest compared to 7% with IH-ECPR, [risk ratio (RR)=0.91; 95% CI 0.79 to 1.06; P = 0.26]. Incorporating the uncertainty associated with this survival rate, and based on the estimated willingness to pay threshold in Qatar, the OH-ECPR was cost-effective with an incremental cost-effectiveness ratio of QAR 464,589 (USD 127,634). Sensitivity and uncertainty analyses confirmed the robustness of the study outcome. This is the first cost-effectiveness evaluation of OH-ECPR versus IH-ECPR in OHCA patients. OH-ECPR is potentially an economically acceptable resuscitative strategy in Qatar. Other Information Published in: Current Problems in Cardiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cpcardiol.2022.101387